REVIEW: REPROGRAMMING OF CANCER CELLS WITH VARIOUS EMBRYONIC MICROENVIRONMENTS - Mektepbayeva , D.; Janzakova , D.; Shaimerdenova , M.; Karapina , O.; Mu , X.; Kenneth , A.; Akilbekova , D. (Eurasian Journal of Applied Biotechnology, 2017)
Recent studies have demonstrated that common factors present in aggressive cancer cells and embryonic progenitors influence cancer aggressiveness. This review will summarize the cancer-related properties of various embryonic microenvironments. The anticancer effects of embryonic microenvironments on various types of cancer cells and tumors are associated with epigenetic alterations and down regulation of tumor-suppressor genes and the Nodal signaling pathway. The ability to reprogram the tumorigenic phenotype of cancer cells depends on the stage and type of embryonic microenvironment, and reprogramming capacity significantly decreases after organogenesis. Understanding the mechanisms underlying the molecular reprogramming of cancer cells in various embryonic models will help identify potential targets for cancer therapy.